Mobile Health Intervention Reduces Sedentary Time and Physical Inactivity in Patients with Cardiovascular Diseases after Discharge: Systematic Review and Meta-Analysis - Ryo Yoshihara; Masahiro Kitamura; Kodai Ishihara; Yuji Kanejima; Kazuhiro P. Izawa (Heart and Mind, 2025)
Background: Long sedentary time and physical inactivity negatively impact patients with cardiovascular diseases (CVD). Although more and more studies are exploring the effects of mobile health (mHealth), whether an intervention using mHealth reduces sedentary time and physical inactivity is controversial. This systematic review aimed to investigate whether mHealth can reduce sedentary time and physical inactivity in patients with CVD via a comprehensive search and evaluation of relevant articles and review of the effects of mHealth on sedentary time and physical inactivity. Methods: We searched articles on three databases PubMed, Web of Science, and CiNii using “mHealth,” “CVD,” and “clinical trials” as keywords. All studies using mHealth to reduce sedentary time and physical inactivity were included. We assessed risk of bias in the included studies and conducted a meta-analysis using a random effects model. Results: After screening 502 articles, we included five randomized controlled trials. In one study, sedentary time was shorter in the intervention group than the control group by 61.5 min/day at 24 weeks. Three studies using physical inactivity as outcome measures were included in a meta-analysis, and the pooled odds ratio was 0.38 (95% confidence interval, 0.22–0.65), favoring the intervention group. All studies showed high risk of performance bias and low risk of selection bias and reporting bias. Conclusion: The mHealth intervention may remind patients with CVD of exercise training and help them reduce sedentary time and physical inactivity. Future studies need to show for how long mHealth can reduce sedentary time and clarify the cost-effectiveness of the mHealth intervention.